Narrative Inquiry as a Viable Method in Language Teaching Research: A Short Analytical Study (Gyanjyoti, 2023)
This paper portrays my personal experience articulating narrative inquiry as a viable research approach to language pedagogy. It brings a personal nostalgia to the epistemic understanding of narrative inquiry. For this, I employed a qualitative research approach in my paper. For the successful accomplishment of the paper, I employed secondary sources; particularly data collected from research articles, books, dissertations, different websites and reports related to narrative research, etc. Within the qualitative continuum, I used the document analysis method and connected it with my own research experiences of using secondary sources of data in narrative research. More specifically, it explored how the research's paradigm was undergoing to bring the narratives as information to systematize the random experiences in research. In particular, this paper offers a metaphorical three-dimensional narrative inquiry space as a way to explore the aesthetic and artistic dimensions of narrative inquiry. Furthermore, narrative inquiry research paves the way to understanding what researchers know and what they believed about their research practices. The core process of narrative research is to systematize its design and set its conceptual framework. The principal attraction of narrative as a method is its capacity to render life experiences, both personal and social, in relevant and meaningful ways. It shows that researchers must learn to assume possible research procedures linearly to address their actions and performance. Moreover, narrative inquiry as a method serves as a pioneering foundation to replicate human experiences and establish itself as a prior research method in educational research.